Bone marrow mesenchymal stem cell-derived exosomes promote plasminogen activator inhibitor 1 expression in vascular cells in the local microenvironment during rabbit osteonecrosis of the femoral head - Li, Lu (Stem Cell Res Ther, 2020)
BACKGROUND: Nontraumatic osteonecrosis of the femoral head (NONFH) is a highly disabling orthopedic disease in young individuals. Plasminogen activator inhibitor 1 (PAI-1) has been reported to be positively associated with NONFH. We aimed to investigate the dysregulating PAI-1 in bone marrow mesenchymal stem cells (BMMSCs) and vascular cells in rabbit steroid-induced NONFH. METHODS: To verify the hypothesis that BMMSCs could promote thrombus formation in a paracrine manner, we collected exosomes from glucocorticoid-treated BMMSCs (GB-Exo) to determine their regulatory effects on vascular cells. microRNA sequencing was conducted to find potential regulators in GB-Exo. Utilizing gain-of-function and knockdown approaches, we testified the regulatory effect of microRNA in exosomes. RESULTS: The expression of PAI-1 was significantly increased in the local microenvironment of the femoral head in the ONFH model. GB-Exo promoted PAI-1 expression in vascular smooth muscle cells and vascular endothelial cells. We also revealed that miR-451-5p in GB-Exo plays a crucial role for the elevated PAI-1. Moreover, we identified miR-133b-3p and tested its role as a potential inhibitor of PAI-1. CONCLUSIONS: This study provided considerable evidence for BMMSC exosomal miR-mediated upregulation of the fibrinolytic regulator PAI-1 in vascular cells. The disruption of coagulation and low fibrinolysis in the femoral head will eventually lead to a disturbance in the microcirculation of NONFH. We believe that our findings could be of great significance for guiding clinical trials in the future. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13287-020-01991-2.